A cross‐sectional study of auditory verbal hallucinations experienced by people with a diagnosis of borderline personality disorder. (25th August 2021) - Hayward, Mark; Jones, Anna‐Marie; Strawson, Will H.; Quadt, Lisa; Larsson, Dennis E. O.; Silva, Marta; Davies, Geoff; Fielding‐Smith, Sarah; Hazell, Cassie M.; Critchley, Hugo D.; Garfinkel, Sarah N.
Abstract: Background: The presence of auditory verbal hallucinations (AVHs) does not currently feature in the main diagnostic criteria for borderline personality disorder (BPD). However, there is accumulating evidence that a high proportion of BPD patients report longstanding and frequent AVHs which constitute a significant risk factor for suicide plans and attempts, and hospitalization. Aim: This study addressed questions about the validity and phenomenology of AVHs in the context of BPD. The longer‐term aim is to facilitate the development and translation of treatment approaches to address the unmet need of this population. Method: This was a cross‐sectional study, combining phenomenological and psychological assessments administered in person and online. We explored the experiences of 48 patients with a diagnosis of BPD who were hearing AVHs. Results: Participants gave 'consistent' reports on the measure of AVH phenomenology, suggesting that these experiences were legitimate. Similar to AVHs in a psychosis context, AVHs were experienced as distressing and appraised as persecutory. AVHs were found to be weakly associated with BPD symptoms. AVHs were also rated highly as a treatment priority by the majority of participants. Conclusion: The findings suggest that AVH is a legitimate and distressing symptom of BPD and a treatment priority for some patients. The relative independence of AVHs from other BPD symptoms and emotional states suggests that psychological treatment may need to be targeted specifically at the symptom of AVHs. This treatment could be adapted from cognitive behaviour therapy, the psychological intervention that is recommended for the treatment of AVHs in the context of psychosis.